2004
DOI: 10.1111/j.1365-2028.2004.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of the Mara Woodlands in Kenya

Abstract: The woodlands of the Masai Mara National Reserve in Kenya have suffered dramatic declines over four decades as a result of elephant and fire pressure. This study examined the current status of woody resources in the Reserve and browse pressure thereon, using both classification (TWIN-SPAN) and ordination (DCA) techniques. From 333 widespread regular plots used to survey the vegetation, a total of 62 woody species were identified. Thirteen woody habitats were identified on the basis of species composition, vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The limited work conducted in the miombo region indicates that fire and elephants together act as a powerful restriction on the recruitment of trees. This ultimately decreases woody vegetation productivity [ Guy , 1981, 1989; Ben‐Shahar , 1998; Mapaure and Campbell , 2002; Walpole et al , 2004; Baxter and Getz , 2005; Ribeiro , 2007; Ribeiro et al , 2008], with consequences for carbon and energy balances [ Houghton , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The limited work conducted in the miombo region indicates that fire and elephants together act as a powerful restriction on the recruitment of trees. This ultimately decreases woody vegetation productivity [ Guy , 1981, 1989; Ben‐Shahar , 1998; Mapaure and Campbell , 2002; Walpole et al , 2004; Baxter and Getz , 2005; Ribeiro , 2007; Ribeiro et al , 2008], with consequences for carbon and energy balances [ Houghton , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the landscape of many types of woodland in Africa have been attributed directly to the interactive effect of elephants and fire (Buechner & Dawkins, 1961;Guy, 1981Guy, , 1989Laws, 1970;Mapaure & Campbell, 2002;Ribeiro et al, 2008a;Sukumar, 2003;Walpole et al, 2004). In general, the pattern of change is the same: as elephants over-browse the woodlands, laying waste to mature trees, there is an increase in the low woody vegetation and grass cover as well as a dramatic increase in fuel load.…”
Section: Ecological Role Of Disturbances In Miombo Woodlandsmentioning
confidence: 73%
“…Dublin et al (1990) studied the effects of elephants and fires in the Serengeti-Mara woodlands in Kenya and found that the combined effect of fire and elephants caused consistently decrease in the recruitment of tree species. Recently Walpole et al (2004) assessed the status of the Mara woodlands (adjacent to the Serengeti National Park). They report that species diversity is relatively low, possibly because of decline in the density and extent of woodland and thickets originated by increasing elephant population within the area.…”
Section: Ecological Role Of Disturbances In Miombo Woodlandsmentioning
confidence: 99%
“…In Ithala, the combination of elephants and browsers pressure was such that plant species composition changed from species with climax state lifecycle traits (long lived, low recruitment) to more pioneer like species (high recruitment, shorter lifespans ) and also promoted the recruitment of less desirable browse species (Wiseman et al, 2004). Other studies have shown that small mammals herbivory is usually not a limiting factor on its own, although it slows regeneration in cases of high densities (Barnes, 2001;Walpole et al, 2004;Western & Maitumo, 2004;Western, 2006). In Kenya's Masaai Mara National Reserve, 73% of woody species were utilised by small browsers, which changed species composition and abundance andfacilitated some invasive species (Walpole et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that small mammals herbivory is usually not a limiting factor on its own, although it slows regeneration in cases of high densities (Barnes, 2001;Walpole et al, 2004;Western & Maitumo, 2004;Western, 2006). In Kenya's Masaai Mara National Reserve, 73% of woody species were utilised by small browsers, which changed species composition and abundance andfacilitated some invasive species (Walpole et al, 2004). In Botswana, small to medium browsers were considered responsible for changing vegetation morphology (Styles & Skinner, 2001).…”
Section: Discussionmentioning
confidence: 99%